2019
DOI: 10.1007/s12253-019-00662-9
|View full text |Cite
|
Sign up to set email alerts
|

All Benign and Malignant Apocrine Breast Lesions Over-Express Claudin 1 and 3 and Are Negative for Claudin 4

Abstract: Invasive apocrine carcinoma of the breast is an uncommon triple negative tumour that lacks a specific therapeutic target. Apocrine metaplasia of the breast shares common morphological features with apocrine carcinoma, and was previously found to consistently over-express claudin 1 and to lack claudin 4. This study was aimed at finding whether apocrine carcinoma, and other related apocrine breast lesions, have similar claudin profile. The immunohistochemical expression of claudin 1, 3 and 4 was studied in 11 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…39 Sousha et al recently demonstrated claudin 1 and claudin 3 expressions and the lack of claudin 4 protein expression in a small cohort of apocrine lesions, including invasive apocrine carcinoma with the triple-negative phenotype. 40 The diagnostic and potential therapeutic utility of these findings remains unknown.…”
Section: Epithelial-to-mesenchymal Transition (Emt) In Apocrine Carci...mentioning
confidence: 99%
“…39 Sousha et al recently demonstrated claudin 1 and claudin 3 expressions and the lack of claudin 4 protein expression in a small cohort of apocrine lesions, including invasive apocrine carcinoma with the triple-negative phenotype. 40 The diagnostic and potential therapeutic utility of these findings remains unknown.…”
Section: Epithelial-to-mesenchymal Transition (Emt) In Apocrine Carci...mentioning
confidence: 99%